Interactions of pleckstrin homology domains with membranes: adding back the bilayer via high throughput molecular dynamics - Yamamoto, E; Kalli, A; Yasuoka, K; Sansom, M (Cell Press, 2016)
In this study we present a multi-scale molecular simulation pipeline for determining the favoured mode of interaction of a pleckstrin homology (PH) domain with a phosphatidyl-inositol-phosphate (PIP)-containing lipid bilayer. This allows us to predict PH/membrane interactions across a number of PH domains of known structure. Using the well-characterised GRP1 PH domain, we evaluate our methodology via comparison with available structural and biophysical data. Coarse-grained simulations are analysed to derive a two-dimensional density landscape for PH/membrane interactions alongside residue contact profiles. Overall, we investigate the membrane localization and interactions of 13 different PH domains, using coarse-grained molecular dynamics simulations. These domains show canonical, non-canonical, and dual PIP binding sites on the surface of the PH domains. Our results demonstrate that the different PH domains associate with the PIP molecules in the membrane via a highly positively charged loop, again in good agreement with available experimental data. Some PH domains are predicted to exhibit modes of interaction with PIPcontaining membranes additional to this canonical binding mode. All 13 PH domains cause a degree of local clustering of PIP molecules upon binding to the membrane. This study provides a global picture of PH domain interactions with membranes. Furthermore, the high-throughput approach has the potential to be extended to other families of peripheral membrane proteins.